Uncoupling of Mitosis and Cytokinesis Upon a Prolonged Arrest in Metaphase Is Influenced by Protein Phosphatases and Mitotic Transcription in Fission Yeast - Chica, Nathalia; Portantier, Marina; Nyquist-Andersen, Mari; Espada-Burriel, Silvia; Lopez-Aviles, Sandra (Frontiers in Cell and Developmental Biology, 2022)
Depletion of the Anaphase-Promoting Complex/Cyclosome (APC/C) activator Cdc20 arrests cells in metaphase with high levels of the mitotic cyclin (Cyclin B) and the Separase inhibitor Securin. In mammalian cells this arrest has been exploited for the treatment of cancer with drugs that engage the spindle assembly checkpoint and, recently, with chemical inhibitors of the APC/C. While most cells arrested in mitosis for prolonged periods undergo apoptosis, others skip cytokinesis and enter G1 with unsegregated chromosomes. This process, known as mitotic slippage, generates aneuploidy and increases genomic instability in the cancer cell. Here, we analyze the behavior of fission yeast cells arrested in mitosis through the transcriptional silencing of the Cdc20 homolog slp1. While depletion of slp1 readily halts cells in metaphase, this arrest is only transient and a majority of cells eventually undergo cytokinesis and show steady mitotic dephosphorylation. Notably, this occurs in the absence of Cyclin B (Cdc13) degradation. We investigate the involvement of phosphatase activity in these events and demonstrate that PP2A-B55Pab1 is required to prevent septation and, during the arrest, its CDK-mediated inhibition facilitates the induction of cytokinesis. In contrast, deletion of PP2A-B56Par1 completely abrogates septation. We show that this effect is partly due to this mutant entering mitosis with reduced CDK activity. Interestingly, both PP2A-B55Pab1 and PP2A-B56Par1, as well as Clp1 (the homolog of the budding yeast mitotic phosphatase Cdc14) are required for the dephosphorylation of mitotic substrates during the escape. Finally, we show that the mitotic transcriptional wave controlled by the RFX transcription factor Sak1 facilitates the induction of cytokinesis and also requires the activity of PP2A-B56Par1 in a mechanism independent of CDK.